New graduate occupational therapists' narratives of ethical tensions encountered in practice. (11th December 2018) - Hazelwood, Tori; Baker, Amy; Murray, Carolyn M.; Stanley, Mandy
Abstract : Background/aim: Professionals in health and social care have high workloads and are working with diverse populations in hierarchical and complicated service delivery systems. There is increasing pressure on new graduates because they are expected to be immediately work ready and may not receive adequate support or supervision. It is well known that there can be issues with satisfaction and retention rates of new graduates due to the challenges they experience. Ethical tensions are an unavoidable part of occupational therapy practice and may contribute to unique challenges for new graduates who may not yet have the personal resources to make sense of these independently. New graduate occupational therapy perceptions of ethical tensions have not yet been explored and this study sought to fill this gap. Exploring the ethical tensions experienced by new graduates can inform appropriate policies, procedures, preparedness and standards. Methods: A qualitative study using narrative enquiry was undertaken in which stories were gathered from eight new graduate occupational therapists who had been working for 6–24 months. Semi‐structured in‐depth interviews were used to gather data. Transcripts were analysed following narrative analysis guidelines. Member checking, reflexivity and keeping an audit trail of methodological and analytical decisions were employed to strengthen the rigour of the study. Results: Analysis revealed six predominant themes: working in a business model, respecting client choice, dealing with aggression and death, mandatory reporting is hard to do, differing team values, and feeling devalued and unsupported. Conclusion: The findings highlight the importance of understanding the ethical tensions faced by new graduates and of exploring ways to assist new graduates to respond constructively to ethical dilemmas, distress and uncertainties. To address the risk of attrition, graduates need systems in place for accessing support to increase preparedness to respond to ethical tensions when they do arise.